2016
DOI: 10.1093/hsw/hlw021
|View full text |Cite
|
Sign up to set email alerts
|

Social Work Should Be More Proactive in Addressing the Need to Plan for End of Life

Abstract: Few people engage in planning for life's end and the prevalence of preparedness is particularly low in ethnic communities. As a profession, social work is well equipped to help increase planning for life's end and the care people wish to receive. However, the profession cannot simply defer to those in hospice and palliative care settings to address this issue. There is a need for earlier and equitable access to death preparation, and social workers can be instrumental in helping to insure equal opportunities f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Another limitation was that this study did not investigate the reasons for the demonstrated connections between personal histories of loss and professional practices, nor did it address gaps in healthcare of culturally diverse populations, an important aspect to consider in overcoming barriers to advance care planning. Studies have found that due to the lack of advance care planning, racial/ethnic minority patients are less likely to be referred to hospice but more likely to receive aggressive treatment at the end of life and die in a hospital (Johnson et al, 2016). Future intervention work building on this research should measure outcomes across culturally diverse populations.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
See 3 more Smart Citations
“…Another limitation was that this study did not investigate the reasons for the demonstrated connections between personal histories of loss and professional practices, nor did it address gaps in healthcare of culturally diverse populations, an important aspect to consider in overcoming barriers to advance care planning. Studies have found that due to the lack of advance care planning, racial/ethnic minority patients are less likely to be referred to hospice but more likely to receive aggressive treatment at the end of life and die in a hospital (Johnson et al, 2016). Future intervention work building on this research should measure outcomes across culturally diverse populations.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Typically, advance directives are not completed with patients in medical or healthcare settings among the older population or people who are terminally ill until the discussion about end-of-life care is initiated. However, death can occur at any age or stage of life (Heyman & Gutheil, 2003; Johnson, Hong, Inoue, & Adamek, 2016). Hence, social workers could be more proactive in supporting adults of any age or disability to plan for end of life (Johnson et al, 2016; Washington et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations